The Effect of Population Growth upon the Quantity of Education Children Receive: A Reply - Miyashita, Hiroshi; Newbold, Paul; Pilarski, Adam M.; Simon, Julian L. (The Review of Economics and Statistics, 1982)
Hiroshi Miyashita, Paul Newbold, Adam M. Pilarski, Julian L. Simon, The Effect of Population Growth upon the Quantity of Education Children Receive: A Reply, The Review of Economics and Statistics, Vol. 64, No. 2 (May, 1982), pp. 352-355